The burden of microstructural damage modulates cortical activation in elderly subjects with MCI and leuko‐araiosis. A DTI and fMRI study. Issue 3 (8th December 2012) - Mascalchi, Mario; Ginestroni, Andrea; Toschi, Nicola; Poggesi, Anna; Cecchi, Paolo; Salvadori, Emilia; Tessa, Carlo; Cosottini, Mirco; De Stefano, Nicola; Pracucci, Giovanni; Pantoni, Leonardo; Inzitari, Domenico; et al.
<x xml:space="preserve">Abstract</x> The term leuko‐araiosis (LA) describes a common chronic affection of the cerebral white matter (WM) in the elderly due to small vessel disease with variable clinical correlates. To explore whether severity of LA entails some adaptive reorganization in the cerebral cortex we evaluated with functional MRI (fMRI) the cortical activation pattern during a simple motor task in 60 subjects with mild cognitive impairment and moderate or severe (moderate‐to‐severe LA group, n = 46) and mild (mild LA group, n = 14) LA extension on visual rating. The microstructural damage associated with LA was measured on diffusion tensor data by computation of the mean diffusivity (MD) of the cerebral WM and by applying tract based spatial statistics (TBSS). Subjects were examined with fMRI during continuous tapping of the right dominant hand with task performance measurement. Moderate‐to‐severe LA group showed hyperactivation of left primary sensorimotor cortex (SM1) and right cerebellum. Regression analyses using the individual median of WM MD as explanatory variable revealed a posterior shift of activation within the left SM1 and hyperactivation of the left SMA and paracentral lobule and of the bilateral cerebellar crus. These data indicate that brain activation is modulated by increasing severity of LA with a local remapping within the SM1 and increased activity in ipsilateral nonprimary sensorimotor cortex and bilateral cerebellum. These potentially adaptive changes as well lack of contralateral cerebral hemisphere hyperactivation are in line with sparing of the U fibers and brainstem and cerebellar WM tracts and the emerging microstructual damage of the corpus callosum revealed by TBSS with increasing severity of LA. Hum Brain Mapp 35:819–830, 2014. © Wiley Periodicals, Inc.